Assessing the quality of email-based and conventional essay writing - BM Bappu, Noor Wati; Abdul Ghani, Rozina (IIUM Press, International Islamic University Malaysia, 2017)
This book investigates the differences in quality between learners’ email-based writing and conventional writing over time. It also looks at the features of email-based writing as well as learners’ perceptions towards email-based writing. Email is an extension mode of writing in line with current educational developments and it should be made known to all levels of learners in urban as well as rural areas. This study meets the aspiration of the Ministry of Education as the English language syllabus incorporates globalization and Information and Communications Technology (ICT) into the learning outcomes. The study adopts a time-series design. Both qualitative and quantitative data are gathered for the study. The subject for this research book is a class of 32 Form Four learners from Sekolah Menengah Kebangsaan Hwa Lian, a secondary school in Mentakab, Pahang. In the book, writing activities were carried out in 18 weeks. In the first eight weeks, writing were conducted in class using the conventional (pen-and-paper) way. Email-based writing activities were conducted in the computer laboratory for the following eight weeks (weeks 11 – 18). The tasks given were evaluated based on the writing conventions and English language accuracy guidelines provided by the Ministry of Education. For the email-based writing activity, learners were given a topic to write at the beginning of the class. They had to type their essays using email and send them via email to the teacher. Learners spent their class time typing their essays; they were allowed to use the Internet to gather information. In cases where they were not able to finish their essays within the class period, they were allowed to finish them over the weekend. Learners’ essays were examined and analysed based on 11 types of errors which were divided into two categories. The errors were based on the SPM writing error code. The findings showed that email-based writing has its own worth that can create a learning environment that is gratifying, intriguing and fun to learners. Email discourse constitutes linguistic features that are both written and spoken in nature. The quality of email writing is further supported by the encouraging attitude of the learners towards this mode of writing.